ผลของการให้ข้อมูลย้อนกลับงานเขียนโครงการฝึกอบรม ของนักศึกษาระดับปริญญาตรี - บุญมี, จิรวรรณ; บุญมี, ธวัชชัย (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาผลของการให้ข้อมูลย้อนกลับงานเขียนโครงการฝึกอบรมของนักศึกษาชั้นปีที่ 3 ภาคปกติ ระดับปริญญาตรี สาขาวิชาการจัดการ ภาควิชาบริหารธุรกิจ คณะวิทยาการจัดการ มหาวิทยาลัยราชภัฏเชียงใหม่ ที่เรียนรายวิชาเทคนิคการฝึกอบรมและการประชุมในภาคเรียน 1/2557, 1/2558 และ 1/2559 ผลการวิจัยพบว่าวิธีการให้ข้อมูลย้อนกลับที่แตกต่างกัน 3 แบบซึ่งนำไปใช้ในแต่ละภาคเรียนส่งผลให้คะแนนงานเขียนโครงการฝึกอบรมของนักศึกษาแตกต่างกันที่ระดับนัยสำคัญ 0.05 กล่าวคือ ในภาคเรียน 1/2558 ใช้วิธีการให้ข้อมูลย้อนกลับโดยการตรวจชิ้นงานเป็นรายบุคคล และการให้ข้อมูลย้อนกลับด้วยวาจาในชั้นเรียนร่วมกับวิธีสอนแบบปกติ และในภาคเรียน 1/2559 ใช้วิธีการให้ข้อมูลย้อนกลับโดยการตรวจชิ้นงานเป็นรายบุคคล และการให้ข้อมูลย้อนกลับด้วยวาจาในชั้นเรียน ประกอบการให้ข้อมูลย้อนกลับโดยการใช้สื่อภาพถ่ายชิ้นงานร่วมกับวิธีสอนแบบปกติ ซึ่งการให้ข้อมูลย้อนกลับทั้ง 2 วิธีดังกล่าวข้างต้น ส่งผลให้คะแนนเฉลี่ยสูงกว่าวิธีสอนแบบปกติโดยไม่มีการให้ข้อมูลย้อนกลับในภาคเรียน 1/2557 อย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 คำสำคัญ: การให้ข้อมูลย้อนกลับ ทักษะการเขียน โครงการฝึกอบรม ABSTRACT The objective of this research was to study the effects of feedback provision on training project writing of the third year undergraduate students majoring in management, Department of Business Administration, Faculty of Management Sciences, Chiang Mai Rajabhat University. These students were studying technique in training and conference subject in the first semesters of 2014, 2015 and 2016 academic years. The research result showed that three different types of feedback provision methods were given and they yielded different scores with the significant level at 0.05. The feedback methods utilized in the first semester of 2015 consisted of individual checks and in-class verbal feedbacks with the normal teaching method, while those used in the first semester of 2016 were composed of individual checks and in-class verbal feedbacks with the work piece photographing media and the normal teaching method. Both methods resulted in higher average scores with a significant level of 0.05 than the method used in the first semester of 2014, which consisted of only the normal teaching method without feedback provision. Keywords: Feedback, Writing Skill, Training Project